1988
DOI: 10.1104/pp.86.1.224
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Decarboxylase, Polyamines, and Pyrrolizidine Alkaloids in Senecio and Crotalaria

Abstract: When tested for ornithine and arginine decarboxylases, pyrrolizidine alkaloid-bearing Senecio riddellii, S. longilobus (Compositae), and Crotalaria retusa (Leguminosae) plants exhibited only ornithine decarboxylase activity. This contrasts with previous studies of four species of pyrrolizidine alkaloid-bearing Heliotropium (Boraginaceae) in which arginine decarboxylase activity was very high relative to that of ornithine decarboxylase. Unlike Heliotropium angiospermum and Heliotropium indicum, in which endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Evidence in the literature suggested that these inhibitors can be uptaken by callus [3,5], cell suspension [4] and protoplast cultures [7], by root fragments [12] and decapitated shoots [2]. We found in media solidified with 0.8% agar a poor uptake of ~4C-DFMO by rooted white clover plantlets.…”
Section: Introductionmentioning
confidence: 75%
“…Evidence in the literature suggested that these inhibitors can be uptaken by callus [3,5], cell suspension [4] and protoplast cultures [7], by root fragments [12] and decapitated shoots [2]. We found in media solidified with 0.8% agar a poor uptake of ~4C-DFMO by rooted white clover plantlets.…”
Section: Introductionmentioning
confidence: 75%
“…Most of the published work on extraction of polyamines from various plant tissues involves homogenization in cold perchloric acid (PCA) or trichloroacetic acid (TCA) using either one of the following: a) chilled mortar and pestle with liquid nitrogen, b) polytron or tissumizer, or c) small conical ground-glass homogenizers with matching pestles (Birecka et al 1988, Faure et al 1991, Kushad and Yelenosky 1987, Maki et al 1991, Meijer and Simmonds 1988, Minocha et al 1991, 1992, Nielsen 1990, Rastogi and Davies 1989, Torrigiani et al 1987. Even though any of these extraction procedures is not too complicated when relatively few samples need to be processed, they are definitely time consuming and occasionally noisy due to the use of polytron for longer periods.…”
mentioning
confidence: 99%